Enhancing accommodation selection: an analysis of simple additive weighting and rank order centroid - Singgalen, Yerik Afrianto (Jurnal Teknik Informatika C.I.T Medicom, 2024)
This study deploys Simple Additive Weighting (SAW) and Rank Order Centroid (ROC) in selecting accommodations. The research problem investigates the efficacy and applicability of these methods in aiding decision-makers, mainly tourists, in choosing accommodations based on diverse criteria. To address this issue, a comprehensive comparative analysis was conducted utilizing both SAW and ROC methodologies to evaluate a range of accommodations in the vibrant tourism destination of Raja Ampat, Indonesia. The SAW method involved the assignment of weights to various criteria and the subsequent calculation of overall scores for each accommodation. In contrast, the ROC method utilized a centroid-based approach to rank the accommodations. The findings underscore notable distinctions between the two methodologies, with SAW providing a detailed assessment of accommodations based on weighted criteria, whereas ROC offers a simplified ranking system. Additionally, the research identified Nyande Raja Ampat as the top-ranked accommodation with a score of 0.95859128, followed by Raja Ampat Sandy Guest House (score: 0.924445677) and Mambetron Homestay Raja Ampat (score: 0.861666825). Warahnus Dive Homestay and Hamueco Raja Ampat Resort secured the fourth and fifth ranks, with scores of 0.831961086 and 0.827113234, respectively. These findings offer valuable insights for tourists seeking accommodations in Raja Ampat and contribute to the broader understanding of decision-making methodologies in the tourism industry.